Crohn's disease therapeutic dietary intervention (CD-TDI): study protocol for a randomised controlled trial. Issue 1 (19th January 2022) - Raman, Maitreyi; Ma, Christopher; Taylor, Lorian M; Dieleman, Levinus A; Gkoutos, Georgios V; Vallance, Jeff K; McCoy, Kathy D; Lewis, Ian; Jijon, Humberto; McKay, Derek M; Mutch, David M; Barkema, Herman W; et al.
Abstract : Introduction: Dietary patterns that might induce remission in patients with active Crohn's disease (CD) are of interest to patients, but studies are limited in the published literature. We aim to explore the efficacy of the CD therapeutic dietary intervention (CD-TDI), a novel dietary approach developed from best practices and current evidence, to induce clinical and biomarker remission in adult patients with active CD. Methods and analysis: This study is a 13-week, multicentre, randomised controlled trial in patients with mild-to-moderate active CD at baseline. One hundred and two patients will be block randomised, by sex, 2:1 to the intervention (CD-TDI) or conventional management. Coprimary outcomes are clinical and biomarker remission, defined as a Harvey Bradshaw Index of <5 and a faecal calprotectin of <250 µg/g, respectively. Secondary outcomes include gut microbiota diversity and composition, faecal short-chain fatty acids, regulatory macrophage function, serum and faecal metabolomics, C reactive protein, peripheral blood mononuclear cell gene expression profiles, quality of life, sedentary time and physical activity at 7 and/or 13 weeks. Predictive models of clinical response to a CD-TDI will be investigated. Ethics and dissemination: The research protocol was approved by the Conjoint Health Research Ethics Board at the University of Calgary (REB19-0402) and the Health Research Ethics Board—Biomedical Panel at the University of Alberta (Pro00090772). Study findings will be presented at national and international conferences, submitted for publication in abstracts and manuscripts, shared on social media and disseminated through patient-education materials. Trial registration number: NCT04596566 .